Innate and acquired resistance to African trypanosomiasis - Black, Samuel J.; Seed, J.R.; Murphy, N.B. (2001)
The review discusses the current field status of human and bovine trypanosomiases, and focuses on the molecular basis of innate and acquired control of African trypanosomes in people, cattle and Cape buffalo